Fetal umbilical artery Doppler to predict compromise of fetal/neonatal wellbeing in a high risk population: systematic review and bivariate meta-analysis. (16th November 2010) - Morris, RK; Malin, GL; Robson, SC; Kleijnen, J; Zamora, J; Khan, KS
Abstract : Objective: To determine the accuracy of fetal umbilical artery Doppler for prediction of risk of compromise of fetal/neonatal wellbeing in a high risk population. Design: Systematic review with bivariate meta-analysis. Data Sources: Medline, Embase, Cochrane library, Medion (inception-March 2009), hand searching of relevant journals, reference list checking of included articles, contact with experts. Eligibility Criteria for Selecting Studies: Two reviewers independently selected articles without language restrictions. Criteria for selection were observational studies with umbilical artery Doppler used in a high risk pregnant population with an outcome measure for compromise of fetal/neonatal. Results: 104 studies met the selection criteria (19 191 fetuses). Umbilical artery Doppler showed better prediction of small for gestational age (pooled LR+ 3.76 (2.96, 4.76), pooled LR− 0.52 (0.45, 0.61)) and for compromise of fetal/neonatal wellbeing (pooled LR+ 3.41 (2.68, 4.34), pooled LR− 0.55 (0.48, 0.62)) in a high risk population. This group also showed useful accuracy for prediction of intrauterine death (pooled LR+ 4.37 (0.88, 21.8), pooled LR− 0.25 (0.07, 0.91)), acidosis (pooled LR+ 2.75 (1.48, 5.11), pooled LR− 0.58 (0.36, 0.94)) and admission to neonatal intensive care (pooled LR+ 3.35 (2.58, 4.36), pooled LR− 0.46 (0.39, 0.55)). Conclusion: Fetal umbilical artery Doppler is a moderately useful test in a high risk population to predict mortality and risk of compromise.